Determination of flavonoids in Centella asiatica (L.) urban and their utilization in herbal noodle - Mohd Zainol, Mohamad Khairi (2004)
‘Pegaga’ or Centella asiatica has been medically recognized to be effective in the treatment of skin diseases and many other illnesses. Due to the presence of abundant amount of active compounds, C. asiatica is potentially a good source to alleviate or prevent the development of chronic diseases, cancer and others. The objective of this study was to develop and optimize a functional food namely C. asiatica herbal noodle containing flavonoids from C. asiatica. The study included determination and quantification of flavonoids (bioactive compounds) and selection of the best formulation using RSM to develop the product containing C. asiatica. The first stage of the study was conducted to evaluate the highest antioxidative activity and total phenolic compounds in different parts namely leaf, root and petiole among four different accessions of C. asiatica namely Ca 10, CA 05 Ca 08 and CA 11 with the objective to determine the best accession that would then be used in the developed products. Methanol was used as an extraction solvent and antioxidative assay was biochemically done using ferric thiocyanate method (FTC) and thiobarbituric acid test (TBA) while total phenolic compounds (TPC) was determined using the Folin- Ciocalteu phenol method. Results from FTC and TBA test showed that no significant (p<0.05) difference was exhibited in antioxidative activity between leaf extract of C. asiatica especially CA 05 as compared to that of α-tocopherol and BHT while petiole extracts showed somewhat negligible activity. On the other hand, the antioxidative activities measured correlated well with total phenolic compounds (TPC) for leaf extract of CA 05. Therefore leaf of CA 05 was used for further analysis to determine the compound responsible for the high antioxidative activities. The results also suggested that more than one compound attributed to antioxidative activity of different parts of C. asiatica and flavonoids are one of phenolic compounds that were known to be potent antioxidant that might be responsible for the antioxidative activities in C. asiatica. Further study was done to determined the stability of flavonoids (catechin, quercetin and rutin) during drying and to identify the optimum drying method that could sustained the most flavonoids in C. asiatica which were then incorporated into food product. Reverse-phase high-pressure liquid chromatography (RP-HPLC) with a Symmetry C18 column (Waters, USA) and a water/methanol mobile phase was used to determine individual flavonoids in leaf C. asiatica CA 05. The results showed that vacuum oven drying method was the optimum treatment among the different drying techniques based on factors of cost and yield of flavonoids sustained. The next area of study was focused on incorporating C. asiatica into the product, analyzed for bioactive compound present in it and tested for consumer acceptance. Response surface methodology (RSM) using Central Composite Design with quadratic model was used to in the product formulation, development and optimization. Three independent variables were chosen (C. asiatica extract, salt and sodium hydroxide or ‘air abu’) in the development and optimization of the product. Finally, the products were analyzed for the presence of flavonoids and the sensory evaluation (dependent variables). C. asiatica herbal noodles containing pegaga extract (formulation of: 10% C. asiatica extract, 5g salt and 5g ‘air abu’) was the most optimum product based on the dependent variables collected. This research would then be able to serve as reference for new products in the food industry and wider the selection of consumption of natural products.